Critique of Forest Intelligence - Giovanni La Varra; Alberto Cervesato; Tommaso Antiga (Footprint)
This contribution starts from a question: in what terms can the design reason that is guiding the action of numerous contemporary architects, city planners and project makers be considered and defined? We argue that that such reason can be defined as ‘forest intelligence’, opposed to the human-animal intelligence that has instead characterised the repertoire of architectural-urban solutions from modernity onwards. The latter is characterised by verticality, exemplified by classes of opposites such as centre and periphery, the space of ‘nature’ and the space of the ‘city’. On the other hand, the new ‘forest intelligence’ is characterised by horizontality – urban polycentrism, interrelation between the parts of the city, absence of a clear division between ‘natural’ and urban space. Therefore, we have investigated three remarkable moments of the first quarter of our century. From the art world, the Documenta 13 exhibition (2012); representing architecture and landscape design, Gilles Clément’s Manifeste du Tiers paysage (2004); and from the field of politics, the ‘New Landscape Declaration’ (2016), an updated manifesto for landscape practice. We believe that these three specific and topical events can be understood as activators, initiators and at the same time as spaces for publicising the aforementioned ‘forest intelligence’.